ASSESSING UPLAND RICE, BIOCHAR AND SOIL NUTRIENT MODULES IN THE GUINEAN SAVANNA ZONE (NYANKPALA) GHANA (Proceedings of the International Conference on Agriculture, 2022)
The Agricultural Production System simulator (APSIM) is a cropping modeling program that is employed to address research on intercropping systems. We tested it in the Guinea Savannah zone to increase nutrient and nutrient use efficiency to alter agricultural practices in rice-based farming system. Our approach was to calibrate and test the models Upland rice (Oryza sativa L.) and cowpea (Vigna unguiculata L.) intercrop, the interactions between crop growth and soil nitrogen (N), surface organic matter, biochar and the assessment of model projections against independent data sets. During calibration, parameters for crops and soil were developed to ensure that the model adequately captures soil nutrient dynamics under three different biochar plus half rate of inorganic fertilizer root mean square error (RMSE). Soil inorganic N dynamics RMSE 0.18 and 0.216 kg N ha-1 for 2018 and 2019 respectively, contrasting soil N mineralization patterns under the combination of biochar and inorganic fertilizer applications RMSE 3.86 and 3.18 kg N ha-1 for 2018 and 2019 respectively, straw N uptake RMSE 6.71 and 6.67 kg N ha-1 for 2018 and 2019 respectively, grain N uptake RMSE 478.62 and 605.33 kg ha-1 for 2018 and 2019 respectively. The calibrated model was evaluated against independent data on grain yield RMSE 315.18 and 460.04 kg ha-1 for 2018 and 2019 respectively, straw production RMSE 183.64 and100.08 kg ha-1 for 2018 and 2019 respectively and with a highly acceptable yield, particularly with respect to return-N relations. APSIM has proven to be a reliable model for research and decision-making to improve production systems in upland rice-cowpea intercrop in Nyankpala.
Keywords: Agricultural Production System simulator (APSIM); nutrient use efficiency; biochar; intercropping